Assessing Community Needs and Expectations with Healthcare Quality: A Case Study of Lawawoi Community Health Center - Muhammad Tahir; Hasrul Hasrul; Nur Annisa Parno; Asnuddin Asnuddin (Journal of Public Health and Pharmacy, 2025)
Introduction: In this study, we aimed to examine the relationship between community healthcare needs, expectations, and perceived service quality within the context of rural health service delivery. With growing global emphasis on patient centered care and rising concerns about inequitable healthcare access, our objective was to assess how well community needs and expectations align with service provision at the Lawawoi Community Health Center (CHC) to address gaps identified in existing literature.